Increased Serum Levels and Chondrocyte Expression of Nesfatin-1 in Patients with Osteoarthritis and Its Relation with BMI, hsCRP, and IL-18 - Lifeng Jiang; Jiapeng Bao; Xindie Zhou; Yan Xiong; Lidong Wu (Mediators of Inflammation)
Background. Adipokines have been proved to relate with osteoarthritis (OA). As a recently discovered adipokine, nesfatin-1 relationship with OA has not been reported. Aim. To determine the levels of nesfatin-1 in serum and synovial fluid (SF) from patients with and without OA; to examine the correlation between nesfatin-1 levels and high sensitivity C-reactive protein (hsCRP), Type IIA Collagen N Propeptide (PIIANP), and IL-18 (interleukin-18) levels in serum or synovial fluid. Methods. Serum and SF were collected from knee OA patients and healthy persons, respectively. Five articular tissues were obtained during TKR for immunohistochemistry (IHC). Nesfatin-1 levels, hsCRP, PIIANP, and IL-18 in serum and SF were analyzed by enzyme-linked immunosorbent assay (ELISA). Results. Nesfatin-1 gene was expressed in OA-affected articular cartilage. OA serum contained significantly higher levels of nesfatin-1, as compared to serum from healthy controls (), and nesfatin-1 levels in OA serum exceeded those in paired SF samples (). Significant correlation was found between serum nesfatin-1 and hsCRP levels in OA patients (, ) and also synovial nesfatin-1 and IL-18 levels (, ). Conclusion. Nesfatin-1 is present in articular tissues and may contribute to the physiopathologic changes in OA. Nesfatin-1, accompanied with hsCRP and IL-18, could be new molecular makers to speculate OA progression.